Study on Preparation and Processing Properties of Mechano-Chemical Micro-Grinding Tools - Xin Song; Feifan Ke; Keyi Zhu; Yinghui Ren; Jiaheng Zhou; Wei Li (Applied Sciences, 2023)
The application of hard and brittle materials such as single-crystal silicon in small parts has expanded sharply, and the requirements for their dimensional accuracy and processing surface quality have been continuously improved. This paper proposes using mechano-chemical micro-grinding tools to process single-crystal silicon, which can realize the high-quality and efficient processing of such tiny parts through mechano-chemical composite action. The microstructure composition of the mechano-chemical micro-grinding tools was designed, the theoretical analysis model of grinding force was established and verified by experiments, and the temperature field distribution during mechano-chemical micro-grinding of single-crystal silicon was simulated and studied, which provided a theoretical basis for mechano-chemical action. Special micro-grinding tools were developed, and mechano-chemical micro-grinding processing tests were carried out. The results show that the coupling synergy of grinding force and grinding temperature improves the chemical activity of the micro-grinding tools, thereby promoting the solid–solid phase chemical reaction of abrasives and additives at the sharp points of the surface of the micro-grinding tools. And when the content of cerium oxide abrasive is 25%, it is more conducive to the solid–solid phase chemical reaction, and calcium oxide can be used as an additive to promote the active agent of solid–solid phase chemical reaction, improve the degree of chemical reaction, and thus improve the removal rate of materials. Soft reactants that are easy to remove are generated on the surface of monocrystalline silicon and are removed by the mechanical friction between the abrasive grain and the surface of the silicon wafer, and finally achieve low-damage processing with a surface roughness of Ra1.332 nm, which is much better than the surface roughness of Ra96.363 nm after diamond abrasive processing.